Social Media as a Marketing Tool : Opportunities and Challenges - Yadav, Mayank (Indian Journal of Marketing, 2017)
It has been observed that Internet technologies and web-based applications are persistently increasing and in the current scenario, technology is more about linking people rather than linking customers. Social media usage has escalated in the past few years, which has made it easier for firmsÂ and consumers to intermingle with each other and their friends and make it further easier to communicate with a large audience. In the findings of a study conducted by McKinsey Global Institute, it was revealed that 1.5 billion people use social networking sites, and out of these, 80% interact regularly with other social media users. The popularity of social media has made 70% companies use social media actively. Social media has now reached a place where it is seen as a way of life to socialize and conduct business. However, social media, apart from being an effective tool for interaction, has got risks attached to it. This conceptual paper focused on introducing the key terms, concepts, relevance, benefits, and hazards of employing social media as a marketing instrument. It also aimed to discuss how social media affects a firm’s performance and marketing strategy. This paper highlighted the problems that companies may face by adopting social media as a marketing tool and the managerial implications of it with the help of few cases.